Not your ordinary faerie tale - Warren, Christine (New York : St. Martins Paperbacks, 2011)
After her two best friends marry a blood-sucking vampire and a furry-faced werewolf, a reporter vows no interspecies dating until she meets Luc, the captain of the Fae Queen's Guard, who needs her skills to locate some evil villains.
Keywords: Reporters and reporting -- Fiction; Fairies -- Fiction; Supernatural -- Fiction; Occult fiction; Love stories